Accidental organophosphate poisoning: A case series of 2 pediatric coumaphos exposures. Issue 6 (1st December 2022) - Seltzer, Justin A.; Friedland, Sarah; Friedman, Nathan A.; Winkler, Garret A.; Foreman, Emily; Al Mubarak, Yousef; Buccine, Brent; Engorn, Branden; Kreshak, Allyson; Minns, Alicia; Tomaszewski, Christian A.; Lasoff, Daniel R.; et al.
Abstract: Introduction: Pediatric organophosphate insecticide poisonings are rare in the United States, and life‐threatening toxicity is rarely seen. We report 2 accidental ingestions of the organophosphate insecticide coumaphos that resulted in life‐threatening symptoms. Case Reports: A 7‐year‐old boy and 10‐year‐old girl both presented from home after accidental ingestion of 1 "spoonful" of coumaphos 20% liquid (Asuntol; Bayer de Mexico, S.A. de C.V., Mexico D.F., Mexico). There were no other known ingestions. Both became rapidly symptomatic, with the boy developing dyspnea, vomiting, and depressed mental status and the girl developing headache and nausea. Soon afterward, the boy had witnessed cardiopulmonary arrest and the girl developed altered mental status and flaccid paralysis. Both were treated initially with atropine, but required no additional doses. On arrival to the pediatric intensive care unit (ICU), both patients received pralidoxime with subsequent plasma exchange and continuous venovenous hemodiafiltration (CVVHDF). Transient anemia, coagulopathy, transaminitis, and hyperglycemia developed in both patients. The girl was extubated on hospital day 6 and the boy on hospital day 11. The girl's course was complicated by aspiration pneumonia and an isolated seizure. The boy's course was complicated mainly by anoxic brain injury, associated seizures, neuroagitation, spasticity, and autonomic instability. The girl was discharged on hospital day 16 and remains asymptomatic 32 days after ingestion. As of 90 days after ingestion, the boy remains admitted to inpatient rehabilitation. Discussion: The clinical benefit of pralidoxime, plasma exchange, and CVVHDF is uncertain in these cases. The optimal treatment regimen for organophosphate insecticide toxicity remains poorly defined.